2018
DOI: 10.1016/j.survophthal.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and ocular fluid compounds as potential biomarkers in age-related macular degeneration

Abstract: Biomarkers can help unravel mechanisms of disease and identify new targets for therapy. They can also be useful in clinical practice for monitoring disease progression, evaluation of treatment efficacy, and risk assessment in multifactorial diseases, such as age-related macular degeneration (AMD). AMD is a highly prevalent progressive retinal disorder for which multiple genetic and environmental risk factors have been described, but the exact etiology is not yet fully understood. Many compounds have been evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
130
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 368 publications
(637 reference statements)
4
130
0
1
Order By: Relevance
“…TGF‐β is found to increase the expression of VEGF and is therefore also implicated as an angiogenic factor . Cross‐sectional studies found conflicting results whether measurements of systemic and local angiogenic factors differ between AMD patients and controls . Currently, there are no prospective cohorts that have measured angiogenic factors to predict disease progression in AMD.…”
Section: Molecular Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…TGF‐β is found to increase the expression of VEGF and is therefore also implicated as an angiogenic factor . Cross‐sectional studies found conflicting results whether measurements of systemic and local angiogenic factors differ between AMD patients and controls . Currently, there are no prospective cohorts that have measured angiogenic factors to predict disease progression in AMD.…”
Section: Molecular Risk Factorsmentioning
confidence: 99%
“…LDL are lipoproteins (see section Lipoproteins) that are an easy target for oxidation by free radicals. While some cross‐sectional studies show increased levels of systemic ox‐LDL in AMD patients, only two prospective cohorts have investigated the relationship between systemic ox‐LDL and disease progression and found no correlation …”
Section: Molecular Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Choroidal neovascularization (CNV) is a major characteristic of wet age-related macular degeneration (AMD) and is one of the most common causes of irreversible blindness in people over 60 years old in western countries [1]. Recent studies indicate that CNV is a complex process in which the degeneration of retinal blood vessels in the elderly leads to tissue ischemia and hypoxia; therefore, hypoxia-mediated signaling is thought to be involved in the progression of the wet form of AMD [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the classical view, the RPE, including the Bruch's membrane (BM), was the only pathological site to be considered in AMD. However, more recent data strongly suggest a much more active role of the choroid, photoreceptors, and the blood system in the development of AMD than previously thought (6)(7)(8). A main stream AMD hypothesis is that nonpathalogical agerelated retinal changes insidiously turn in into pathological (dry) AMD changes, while a more sudden twist on top of the ongoing pathology causes (wet) AMD (9,10).…”
Section: 2mentioning
confidence: 99%